Observing the mechanism of delayed collapse in colloidal gels: Yielding while becoming stronger - Rui Cheng; Malcolm A. Faers; Francesco Turci; Abraham Mauleon-Amieva; Tanniemola B. Liverpool; Robert L. Jack; C. Patrick Royall (Proceedings of the National Academy of Sciences, 2026)
The delayed collapse of colloidal gels is a vexing problem. Although the equilibrium behavior of colloid-polymer mixtures is well understood, that of far-from-equilibrium gels is surprisingly complex. As the gels age, they become stronger due to coarsening but exhibit no other macroscopic change. Quite counterintuitively for a material whose strength increases with time, gels may undergo sudden, catastrophic collapse under gravity, sometimes weeks or even years after preparation. An understanding of such delayed collapse has long remained elusive. Here, we probe delayed collapse using a variety of techniques across a range of length scales, from time-lapse imaging, particle-image velocimetry, and in situ vane rheology at the macroscopic scale to multiscale confocal microscopy, with which we image a complete sample with a microscopic level of detail. The insight obtained enables us to identify a mechanism for delayed collapse: increased heterogeneity at the top of the gel leads to droplets of solvent-rich material which are denser than the gel. Upon reaching a sufficient size, these droplets overcome the yield stress of the gel, creating channels in the gel as they fall. When they reach the bottom of the gel, these channels then enable rapid solvent flow and sudden, catastrophic collapse.